A gift of the spirit : reading The souls of Black folk - Wolfenstein, E. Victor (Psychoanalysis and social theory., 2007)
In A Gift of the Spirit, Eugene Victor Wolfenstein offers a reading of W.E.B. Du Bois's The Souls of Black Folk aimed at demonstrating its organic unity and coherence. He takes as his interpretive key the experience of the color line with which Du Bois's narrative begins--the incident from his youth in which a white girl refused his offer of a visiting card. Wolfenstein contends that this instance of misrecognition makes visible an aesthetic and affective configuration involving insult and injury, both racial and personal; anger as the immediate response to the humiliating wound; and, when that anger is suppressed, a melancholy retreat from the site of injury. As Wolfenstein reconstructs it, Souls tells the story of Du Bois's twofold approach to waging the battle for recognition: proud and disciplined resistance to the impositions and injustices of white supremacy; and the development of an intellectual station above the field of battle, where it could be surveyed from on high. With its serious and respectful approach to this canonical work in African American social theory, A Gift of the Spirit is a fitting tribute to the enduring relevance of Du Bois's singular achievement.